Effective Learning Model in Fostering Converts in Padang City: Analysis of Studies and Recommendations in the Artificial Intelligence Era - Japeri, Japeri; Perisya, Fauziyyahh; Yunus, Muhammad; Mengki, Jias (International Journal of Artificial Intelligence Research, 2024)
In the era of Artificial Intelligence, this study seeks to analyze and recommend an effective learning model for fostering converts in Padang City. Using a qualitative literature review method, the research examines various learning models relevant to the socio-cultural context of the Minangkabau community. The findings highlight the need for a holistic and multidimensional approach in supporting the learning process of converts. Models such as andragogy, constructivism, cooperative learning, contextual learning, problem-based learning, experiential learning, and transformative learning have been identified as particularly effective. In addition to the selection of learning models, key factors that determine success include the quality of educators, the relevance of learning materials, and the presence of a supportive learning environment. The integration of Minangkabau local wisdom is also deemed essential in helping converts comprehend Islamic teachings in a culturally sensitive manner. Furthermore, the research emphasizes the importance of psychosocial support, including emotional and social assistance, throughout the development process. Given these findings, the study proposes the development of a comprehensive, phased curriculum, the provision of intensive training for converts, the creation of contextual learning materials, the incorporation of advanced AI technologies in the learning process, the formation of support networks, and the establishment of cross-sector collaborations to enhance the learning experience.